Increasing Donor Endothelial Cell Pool by Culturing Cells from Discarded Pieces of Human Donor Corneas for Regenerative Treatments - Parekh, Mohit (J Ophthalmol, 2019)
PURPOSE: To investigate if the peripheral corneal endothelium that is usually discarded after a corneal transplant could be used for endothelial cell culture. METHODS: Donor corneas (n = 19) with a mean age of 72 years, male : female ratio of 15 : 4, and death-to-preservation time of 10 hours were assessed for endothelial cell density (ECD) and number of dead cells before isolation. Alizarin red staining (n = 3) was performed to check the morphology of cells in the center and periphery. Descemet's membrane-endothelial complex was peeled from the center (8.25 mm) and the periphery (2.75 mm) and plated in two different wells of an 8-well chamber slide with media refreshed every alternate day. The confluence rate was monitored by microscopy. Live/dead analysis was performed (n = 3) at confluence. Tag-2A12 as a monoclonal antibody against peroxiredoxin-6 (Prdx-6) (n = 4), ZO-1 (zonula occludens-1) as a tight junction protein (n = 4), and Ki-67 as a proliferative cell marker (n = 4) were used to characterize the cells at confluence. RESULTS: At confluence, 8.25% average increase in the number of cells was observed from the central zone compared with 16.5% from the peripheral zone. Proliferation rate, hexagonality, Ki-67 positivity, and the cell area did not significantly differ between the groups (p > 0.05). All the proteins corresponding to the biomarkers tested were expressed in both the groups. CONCLUSIONS: Although there are significantly fewer amounts of peripheral cells available after graft preparation for keratoplasty, these cells can still be used for endothelial cell culture due to their proliferative capability. The peripheral cells that are discarded after graft preparation can thus be utilized to increase the donor endothelial cell pool for regenerative treatments.